Recent Advances in Research on Antibacterial Metals and Alloys as Implant Materials - Jiao, Juyang; Zhang, Shutao; Qu, Xinhua; Yue, Bing (Frontiers in Cellular and Infection Microbiology, 2021)
Implants are widely used in orthopedic surgery and are gaining attention of late. However, their use is restricted by implant-associated infections (IAI), which represent one of the most serious and dangerous complications of implant surgeries. Various strategies have been developed to prevent and treat IAI, among which the closest to clinical translation is designing metal materials with antibacterial functions by alloying methods based on existing materials, including titanium, cobalt, tantalum, and biodegradable metals. This review first discusses the complex interaction between bacteria, host cells, and materials in IAI and the mechanisms underlying the antibacterial effects of biomedical metals and alloys. Then, their applications for the prevention and treatment of IAI are highlighted. Finally, new insights into their clinical translation are provided. This review also provides suggestions for further development of antibacterial metals and alloys.